Comparison of seroprevalence of Toxoplasma gondii and environmental factors between schizophrenic and non- psychiatric patients in Hospital Kajang, Malaysia (pdf title) - Juanah, Lovetta Yatta (2012)
Studies suggest an association between Toxoplasma gondii infection and schizophrenia and a high seroprevalence of T. gondii has been detected in psychiatric patients especially schizophrenia cases. This matched case-control study aimed at investigating the seroprevalence of T. gondii and associated environmental risk factors in schizophrenia patients and non-psychiatric controls at Hospital Kajang. A total of eighty-eight (88) schizophrenia patients and eighty-eight (88) non-psychiatric patients were enrolled as cases and controls respectively for this study and matched 1:1 by age,gender and race.Socio-demographic background and environmental risk data of the respondents were obtained from a validated and pre-tested questionnaire adapted from epidemiological questionnaire of the International Agency for Research on Cancer (IARC). Blood sample collected from each individual was centrifuged and analyzed for anti-Toxoplasma gondii IgG and IgM antibodies using Enzyme linked immunosorbent assay (ELISA). Mc-nemar chi-square analysis was used to measure the association between the characteristics of the subjects and T.gondii infection and logistics regression analyses was applied to determine the level of risk involved. From the results, T. gondii antibodies were found in 45 (51%) of the 88 schizophrenia patients and in 27 (30.7%) of the 88 controls. The difference in the seroprevalences was statistically significant among the groups(OR= 2.41; 95% CI:2.16-3.01; p=0.023). The mean (SD) age of schizophrenia patients and control was 39.42 ±11.49 years (range: 18-60 years). For IgM antibodies to T. gondii, both cases and controls had the same level of seropositivity (1.1%). The socio-demographic characteristics among both groups had no significant relationship with T. gondii seroprevalence, (p>0.05). From the Chi- square analysis of environmental factors in both groups, T.gondii infection was significantly associated with several variables among the case and control groups; beef consumption (p= 0.003), pork consumption (p<0.001) and risky cat contact p=0.041).Further logistics regression analysis of these factors showed a significant association with T.gondii; beef consumption (OR=3.852, 95%CI 1.550 - 9.569; p=0.004), pork consumption (OR= 13.089, 95%CI= 4.730 – 36.219;p<0.001) and risky cat contact (OR=4.061, 95%CI=1.985 – 16.745; p<0.047). Hence, it can be explained that beef consumption; pork consumption and cat contact are environmental factors prone to the infection with Toxoplasma gondii parasites.In our study,elements to confirm the association of T. gondii infection and schizophrenia are demonstrated. It also lent further weights to the hypothesis that exposure to T. gondii may be a risk factor for schizophrenia.